Employee Behavior and Job Satisfaction in an Organization Using Herzberg's Two-Factor Model: A Theoretical Study - Joseph, Amal (PT FORMOSA CENDEKIA GLOBAL, 2023)
A person's behaviour encompasses not just how they handle themselves in social situations but also how they express strong emotions like joy, anger, love, and sadness while at work. Organizations consist of groups of people who share a common purpose and work together to realise it. If a business wants to succeed in its mission, it requires the full cooperation and coordination of all its personnel. The efficiency and success of a company hinge on the efforts and outlook of its employees. Changes in behaviour have effects on the group. Psychologist Fredrick Irving Herzberg, or